Search for the lightest scalar top quark in events with two leptons in p(p)over-bar collisions at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (Elsevier B.V., 2008)
Data collected by the do detector at a p (p) over bar center-of-mass energy of 1.96 TeV at the Fermilab Tevatron Collider have been used to search for pair production of the lightest supersymmetric partner of the top quark decaying into bl (nu) over tilde. The search is performed in the ll' = e mu and mu mu final states. No evidence for this process has been found in data samples of approximately 400 pb(-1). The domain in the [M((t) over tilde (1)), M((nu) over tilde)] plane excluded at the 95% C.L. is substantially extended by this search. (c) 2007 Elsevier B.V. All rights reserved.